(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to develop a history learning model based on Artificial Intelligence (AI) that is integrated with Kahoot to improve the historical literacy of students at UPTD SMAN 1 Nosu. The method used is developmental research with a qualitative approach through the stages of analysis, design, implementation, and evaluation. The data were obtained from observations, interviews, and documentation. The data analysis technique in this study uses interactive analysis carried out through three stages, namely data reduction, data presentation, and conclusion drawing. The results show that the integration of AI and Kahoot is able to create adaptive, interactive, and interesting learning. This model is proven to improve students’ abilities in understanding chronology, analyzing sources, and interpreting historical events critically. In addition, student motivation and engagement also increased. Thus, this study still has limitations, particularly in its scope, which was conducted in only one school with a limited number of subjects and its reliance on technology facilities and internet connections in the learning process. Therefore, further research is recommended to involve a wider range of schools, use a more diverse approach, and develop more innovative AI- and Kahoot-based learning models for optimal application in history learning across various educational settings.